‘Enthusiasm’ in Burke’s and Kant’s Response to the French Revolution - Grigoriou, Christos (Conatus - Journal of Philosophy, 2022)
The article sets the most eminent defender of the French Revolution, Immanuel Kant, against its most eminent critic, Edmund Burke, articulating their radically different stance toward the French Revolution. Specifically, this juxtaposition is attempted through the concept of enthusiasm; a psychological state of intense excitement, which can refer to both actors and spectators, to both the motivation of someone, acquiring thus a practical significance, or to their distanced contemplation, thereby acquiring the character of aesthetic appreciation. Using the concept of enthusiasm, Ι aspire to bring out Kant’s and Burke’s radically different approaches to society as well as its history and prospects of progress, ultimately suggesting that enthusiasm can provide a vantage point for the dialogue between the enlightenment and counter-enlightenment theses.